Health status and quality of life of survivors of extra corporeal membrane oxygenation: a cross‐sectional study. (23rd February 2016) - Hsieh, Fong‐Tzu; Huang, Guey‐Shiun; Ko, Wen‐Je; Lou, Meei‐Fang
Abstract: Aims: To understand the influential factors related to quality of life for adult patients who have undergone extra corporeal membrane oxygenation. Background: Extracorporeal membrane oxygenation is an invasive treatment for critically ill patients requiring temporary cardiac or respiratory support. Most studies have focused on survival outcomes for patients; few have evaluated health‐related quality of life. Design: A cross‐sectional design. Methods: Data were collected in 2013 from a convenience sample of adult patients who had survived treatment with extracorporeal membrane oxygenation between 2009–2011. Structured questionnaires collected data about health status. The Short Form 36‐item questionnaire measured quality of life. Results: The 100 participants averaged 48·95 years of age. Pearson's correlation showed two measures of health status had significant correlations with quality of life: the Barthel Index and the Instrumental Activities of Daily Living; two measures had significant negative correlations: Charlson's Comorbidity Index and the Nottingham Health Profile‐part II. Mean scores for the physical and mental component summaries of the Short Form‐36 questionnaire were 49·25 and 48·13 respectively. These component scores had significant negative correlations with the Nottingham health profile‐part II. Stepwise multiple linear regression analysis indicated the number of life areas affected on the Nottingham health profile‐part II was a common factor influencing both the mental and physical component summaries scores for quality of life. Conclusions: Social participation was a common factor influencing quality of life. Examining health status and quality of life of extracorporeal membrane oxygenation survivors can help nurses determine interventions for effectively improving health‐related quality of life.